Female urethral diverticular carcinoma: a case report and review of the literature - Li, Dan; Meng, Fan Hua; Yang, Xu (Frontiers in Oncology, 2025)
ObjectiveTo investigate the etiology, clinical manifestations, treatment methods, and prognosis of urethral diverticulum cancer to enhance understanding of this disease.MethodsThis paper reports a case of urethral diverticulum cancer with “hematuria and dysuria” as the main clinical manifestations. The case is discussed in conjunction with relevant literature.ResultsThe patient initially presented to the gynecology department due to postmenopausal bleeding but was not diagnosed with the disease. Subsequently, the patient developed hematuria and dysuria and was referred to the urology department. MRI indicated urethral diverticulum-like changes with suspected tumorous lesions. Cystourethroscopic biopsy confirmed urethral diverticulum cancer. The patient underwent urethrectomy, and postoperative pathological diagnosis was poorly differentiated urothelial adenocarcinoma.ConclusionUrethral diverticulum cancer is a rare and highly aggressive malignant tumor of the urethra with a poor prognosis. The onset of urethral diverticulum cancer is concealed, and its clinical manifestations are nonspecific and diverse. Preoperative diagnosis is challenging, and imaging studies and cystourethroscopy are the primary preoperative diagnostic methods for urethral diverticulum cancer. Pathology and immunohistochemistry serve as the basis for confirmation of diagnosis. Currently, there is no unified treatment protocol for female urethral diverticulum cancer internationally. For female patients with urethral diverticulum cancer without distant metastasis, surgery remains the primary treatment. For patients with distant metastasis, a combination of surgery, chemotherapy, and radiotherapy may be considered.Genetic testing and targeted immunotherapy offer new approaches for future treatment.